CORRELATION BETWEEN HOMOCYSTEINE AND GLYCATION MARKERS IN DIABETIC KIDNEY DISEASE PATIENTS (Vietnam Journal of Community Medicine, 2026)
Objective: The study aims to evaluate the correlation between homocysteine (representing inflammation-oxidative stress) and glycation indices (representing glucose metabolism).Methods: A descriptive cross-sectional study was conducted on 233 patients with diabetic kidney disease aged 18 years and older, who attended outpatient clinics at the Department of General Examination, University Medical Center Ho Chi Minh City - Campus 2. Clinical characteristics such as age, gender, BMI, blood pressure, and duration of type 2 diabetes were recorded, along with paraclinical parameters including blood lipid profile; glycation indices (fasting plasma glucose, HbA1c, fructosamine, and glycation gap); plasma creatinine and cystatin C to assess estimated glomerular filtration rate (eGFR), UACR to assess albuminuria; and homocysteine.Results: The 233 diabetic kidney disease patients had a mean age of 64.0 ± 10.4 years, with a predominance of females. The mean eGFR was 50.7 ± 25.5 mL/min/1.73 m2, the medan UACR was 341.4 ± 671.5 mg/g, and the mean homocysteine was 14.9 ± 6.2 µmol/L. Homocysteine showed a weak inverse correlation with HbA1c (intracellular glycation) (r = -0.158, p = 0.016) but no correlation with fructosamine (extracellular glycation). Homocysteine also showed a weak inverse correlation with the glycation gap (r = -0.144, p = 0.028).Conclusion: Homocysteine has a weak inverse correlation with HbA1c and the glycation gap, but no correlation with fructosamine. This suggests that homocysteine may affect stable glycation products (HbA1c), but may not affect glycation products with a short half-life.
Keywords: Homocysteine, glycation, HbA1c, fructosamine, glycation gap, diabetic kidney disease.